Left Ventricle Remodeling for Patients with Heart Failure and its Influence on Cardiac Performance - Ahmed, Durra A.; Hussain, Mutaz F.; Saleh, Anmar Z. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Many cardiac diseases can cause cardiac hypertrophy developed by the established cardiac overload, such as long term of uncontrolled hypertension, valvuler disease or congenital anomaly and many more causes. If the cause of hypertrophy persists for long time it will generate heart failure, as a result changes in size, shape and function of the heart which refer as remodeling.Objective: To investigate the types of remodeling in patients with heart failure, and study its relation with cardiac performance.Patients and methods: The study included fifty normal individuals and fifty patients, only those patients who developed hypertrophy and failure were chosen. The study has included the measurements of many cardiac parameters obtained by the echocardiography examination. The measurements have included: Left ventricle internal diameter at diastole (LVIDd), Left ventricle internal diameter at systole ( LVIDs), Peak velocity of early transmitral flow (E), Peak velocity of late transmitral flow (A), Isovolumetric contraction time (ICT), Isovolumetric relaxation time (IRT), Ejection time (ET), Ejection fraction (EF%), myocardial performance Index (MPI), Left ventricle mass index (LVMI ), Posterior wall thickness at diastole ( PWTd), Relative wall thickness ( RWT) and Interventricular septum thickness at diastole (IVSTd).Results: results of remodeling have shown nine patients expressed concentric hypertrophy, thirty seven patients have shown eccentric hypertrophy and only four patients were similar to normal. Many other changes were observed these are an exaggerated ratio of (E/A) goes up to four, an increase in the (LV) volume appeared on its dimension at systole for patients (54.63%), a reduced cardiac output for patients and insignificant small change in relative wall thickness (RWT).Conclusion: In conclusion long term cardiac overload can induce hypertrophy, after a period of time heart failure may ensue. This can influence the shape and size of the heart together with a reduction in its performance.